Employing the cooperative learning method in the cognitive achievement of children's drawings (Journal of the College of Basic Education, 2022)
Cooperative learning is one of the methods of teaching that came from the contemporary educational movement, and which research and studies have proven to have a positive impact on students’ academic achievement. With the emphasis that each member of the group learns the educational material so as to make the student the focus of the teaching and learning process, and that learning takes place in an atmosphere free of tension and anxiety in which the students’ motivation rises significantly (Marai and Al-Hila, 2015: 84).